Review of Fiqh Muamalah and Fatwa DSN MUI Murabahah Financing at BMT on MSME - Mualifah, Leni; Hermawan, Rudi (Universitas Trunojoyo Madura, 2022)
This study discusses the review of Islamic law on murabahah financing by BMT Artha Sejahtera on MSME actors. Departing from the phenomenon of financing that is mostly done by various sharia-based financial institutions, the author then formulates it into two forms of questions 1.) What is the form of murabahah financing by BMT Artha Sejahtera for MSME. 2) What is the Review of Islamic Law on MSME Murabahah Financing at BMT Artha Sejahtera. The aim is to find out the MSME Murabahah Financing at BMT Artha Sejahtera and to find out the Islamic Law Review regarding MSME murabahah financing at BMT Artha.Qualitative research method is a research method in which the author as the key instrument examines the condition of a natural object and expresses it systematically, logically, rationally, and directed. This research is also a type of field research, in which the author directly reviews the social conditions of a society.The results of this study indicate that murabahah financing by BMT Artha Sejahtera for MSME actors is carried out by providing goods or services that can support the business of members as MSME actors based on the provisions and agreements of the murabahah contract between the two parties and according to Islamic law the contract applied by BMT Artha Sejahtera in murabahah financing to MSMEs has complied with the existing terms and pillars.